A rare case report of peri-implant bone necrosis: Mapping the distance of initial peri-implant complication toward a path of success - S K Salaria; Rajni Aggarwal; Veenu Madaan Hans; Mayank Hans (Wolters Kluwer Medknow Publications, 2011)
In the past decade, science of implant placement has greatly advanced and at the same time much success has been experienced with the endosseous implant. Despite the long-term predictability of the implants, however, biological, technical and esthetic complications do occur. The use of osseointegrated implants as a foundation for prosthetic replacement of missing teeth has been highly predictable, but still at present, there is no consensus of how to best manage the complications occurring after implant placement. In this report, we discuss post-insertion complication of bone necrosis and its successful management.